2015
DOI: 10.17015/ejbe.2015.015.05
|View full text |Cite
|
Sign up to set email alerts
|

Bank Size, Risk-taking and Capital Regulation in Bangladesh

Abstract: This study examines the impact of bank size on bank regulatory capital ratios and risk-taking behavior using a panel dataset of 30 Bangladeshi commercial banks over the period 2008-2012. The relationship between bank regulatory capital ratios and bank risk-taking is also examined. For empirical analysis, generalized methods of moments (GMM) panel method are used to explore the relationships among bank size, regulatory capital ratios and risk-taking behavior. Empirical results show that large banks hold lower a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
4
19
0
Order By: Relevance
“…This result is consistent with recent studies that find a negative association between capital requirements and bank risk Rahman et al 2015). The positive association of the Explicit Deposit Insurance dummy variable with bank risk-taking proxies shows that explicit deposit insurance generates moral hazard problems and leads banks to increase risk-taking.…”
Section: Openness and Bank Risk-takingsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with recent studies that find a negative association between capital requirements and bank risk Rahman et al 2015). The positive association of the Explicit Deposit Insurance dummy variable with bank risk-taking proxies shows that explicit deposit insurance generates moral hazard problems and leads banks to increase risk-taking.…”
Section: Openness and Bank Risk-takingsupporting
confidence: 92%
“…The extant literature has focused on the structure of the banking industry (Boyd and Nicolo 2005;Martinez-Miera and Repullo 2010), banking regulations Haq et al 2014;Haq and RichardHeaney 2012;Rahman et al 2015), macroeconomic indicators such as GDP per capita, GDP growth, and inflation (Ali and Daly 2010;Bouvatier et al 2014;Castro 2013;Chaibi and Ftiti 2015;Festić et al 2011), the level of financial development (Vithessonthi 2014), legal institutions (Cole and Turk 2013;Houston et al 2010), financial openness (Bourgain et al 2012;Cubillas and González 2014), national culture , and political institutions ) as significant determinants of cross-country variation in bank risk-taking. We analyze the impact of trade openness on bank risk-taking behavior and add to this literature.…”
Section: Introductionmentioning
confidence: 99%
“…Following recent studies on bank capital and risk, such as Altunbas, Carbo, Gardener, and Molyneux [17], Lee and Hsieh [31], and Rahman et al [42], we include variables to control for bank size (Log_TA), liquidity (Liquid_TA), and level of deposits (Deposits_TA).…”
Section: Data and Variablesmentioning
confidence: 99%
“…The prior evidence showed a mixed result due to the geographical distinctions. Recent studies conducted by Rahman et al (2015) Jacques and Nigro (1997) found that bank size is a significant determinant of risk.…”
Section: Bank Sizementioning
confidence: 99%